2023
DOI: 10.3390/molecules28248111
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of 2,6-Di-tert-butylphenol–Argon by Rotational Spectroscopy

Wenqin Li,
Assimo Maris,
Sonia Melandri
et al.

Abstract: The molecular structure of a van der Waals-bonded complex involving 2,6-di-tert-butylphenol and a single argon atom has been determined through rotational spectroscopy. The experimentally derived structural parameters were compared to the outcomes of quantum chemical calculations that can accurately account for dispersive interactions in the cluster. The findings revealed a π-bound configuration for the complex, with the argon atom engaging the aromatic ring. The microwave spectrum reveals both fine and hyperf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The same kind of splitting was then observed in the 26BP•••argon complex. [12] The analysis of the rotational spectrum of the monomer complexed with argon revealed that breaking the symmetry on a plane perpendicular to the ring did not modify the observed splittings, confirming the nature of the hydroxyl group motion toward the two tert-butyl groups. However, it did not provide additional information on the origin of the fine splitting.…”
Section: Introductionmentioning
confidence: 77%
“…The same kind of splitting was then observed in the 26BP•••argon complex. [12] The analysis of the rotational spectrum of the monomer complexed with argon revealed that breaking the symmetry on a plane perpendicular to the ring did not modify the observed splittings, confirming the nature of the hydroxyl group motion toward the two tert-butyl groups. However, it did not provide additional information on the origin of the fine splitting.…”
Section: Introductionmentioning
confidence: 77%
“…Cosmetics analysis represents a rapidly expanding field of analytical chemistry, as new cosmetic formulations are increasingly in demand on the market and the ingredients required for their production are constantly evolving. In particular, the addition of antioxidants, which are well established in food, beverages, and pharmaceuticals, is becoming increasingly popular in cosmetic preparations, where they can serve as active ingredients, supplements, and stabilizers [1][2][3][4][5][6]. Indeed, their ability to scavenge free radicals provides anti-aging, photoprotective, antimicrobial, and anti-inflammatory action, along with protection against oxidative degradation of product components, such as lipid rancidity [1].…”
Section: Introductionmentioning
confidence: 99%